2020
DOI: 10.1111/jth.14683
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the ISTH/SSC bleeding assessment tool for inherited platelet disorders: A communication from the Platelet Physiology SSC

Abstract: Background Careful assessment of bleeding history is the first step in the evaluation of patients with mild/moderate bleeding disorders, and the use of a bleeding assessment tool (BAT) is strongly encouraged. Although a few studies have assessed the utility of the ISTH‐BAT in patients with inherited platelet function disorders (IPFD) none of them was sufficiently large to draw conclusions and/or included appropriate control groups. Objectives The aim of the present study was to test the utility of the ISTH‐BAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 26 publications
3
84
0
1
Order By: Relevance
“…CPDs showed that epistaxis and cutaneous bleeds most frequently occurred, and that epistaxis and oral cavity bleeding were the most severe bleeding symptoms. 6 Glanzmann thrombasthenia was widely represented in their study population (40%) and their study population had fewer women included (57%) as compared to ours (64%).…”
Section: Association Between Bleeding Score and Laboratory Measuremmentioning
confidence: 54%
See 1 more Smart Citation
“…CPDs showed that epistaxis and cutaneous bleeds most frequently occurred, and that epistaxis and oral cavity bleeding were the most severe bleeding symptoms. 6 Glanzmann thrombasthenia was widely represented in their study population (40%) and their study population had fewer women included (57%) as compared to ours (64%).…”
Section: Association Between Bleeding Score and Laboratory Measuremmentioning
confidence: 54%
“…Since the ISTH-BAT documents large variety of bleeding symptoms, it is also used for the phenotyping of patients. 4,5 Very few studies have reported the bleeding phenotype in adult patients with CPDs 6 and most studies focused on a few specific types of CPD 7,8 or a specific mutation. 9,10 Phenotypic characterization of the whole spectrum of CPDs is necessary, since this could help physicians recognize CPD subtypes and inform new patients on prognostic implications regarding their bleeding phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Most affected individuals do not have a spontaneous hemorrhage, but may develop bleeding complications in case of hemostatic challenges such as traumas or surgery. When present, spontaneous bleedings are prevalently muco-cutaneous (e.g., easy bruising, epistaxis, gum bleeding, menorrhagia, gastrointestinal bleeding) and rarely serious [23]. When a hemorrhagic phenotype is overt, the kind of symptoms may help to differentiate "IPD-" from "non-IPD-bleeding-subjects" (e.g., having coagulopathies).…”
Section: Bleeding Symptoms Do Not Allow Specific Diagnosis Of An Ipdmentioning
confidence: 99%
“…When a hemorrhagic phenotype is overt, the kind of symptoms may help to differentiate "IPD-" from "non-IPD-bleeding-subjects" (e.g., having coagulopathies). In contrast, this criterion is fairly useless in distinguishing among diverse IPDs as symptomatic patients commonly share prevalently mucocutaneous hemorrhages [23].…”
Section: Bleeding Symptoms Do Not Allow Specific Diagnosis Of An Ipdmentioning
confidence: 99%
See 1 more Smart Citation